Phase evolution mechanism of selenium during hydrothermal conversion–atmospheric sulfuric acid leaching of copper anode slimes - Fang Shuling; Rao Shuai; Ma Zhiyuan; Liu Yejian; Tian Lei; Chen Lijie; Liu Zhiqiang; Zhang Liheng (Hydrometallurgy, 2026)

Influences of environmental factors on the microbial community characteristics of bioaerosols in a cold region - Nami Lai; Shuozhen Tian; Silu Wang; Xiaoyan Wang; Ruihan Chen; Yuwei Liu; Huize Yang; Mengying Wang; Xiaoyu Cai; Wanying Yao; Shuling Li; Yue Xiao; et al. (Journal of Environmental Sciences, 2026)

Unveiling the gut-vascular connection: Gut microbiota regulates cardiovascular toxicity induced by combined exposure to PM2.5 and high-fat diet via butyric acid/NLRP3 pathway - Jiayu Tian; Jiaji Cheng; Huan Yang; Zeyu Niu; Lifang Zhao; Linlin Guan; Nannan Liu; Shuling Rong; Caihong Wang; Dongxing Shi; Huiqiu Zheng; Na Cao; et al. (Journal of Hazardous Materials, 2025)

Delayed Detached-Eddy Simulations of Aerodynamic Variability During Carrier-Based Aircraft Landing with a Domain Precursor Inflow Method - Jiawei Fu; Ruifan Hu; Hong Wang; Ke Xu; Shuling Tian (Journal of Marine Science and Engineering, 2025)
Flight tests and wind tunnel experiments face difficulties in investigating the impact of aircraft carrier air-wake on the landing process. Meanwhile, numerical methods generally exhibit low overall computational efficiency in solving such problems. To address the computational challenges posed by the disparate spatiotemporal scales of the ship air-wake and aircraft motion, a domain precursor inflow method is developed to efficiently generate unsteady inflow boundary conditions from precomputed full-domain air-wake simulations. This study investigates the aerodynamic variability of carrier-based aircraft during landing through the turbulent air-wake generated by an aircraft carrier, employing a hybrid RANS-LES methodology on dynamic unstructured overset grids. The numerical framework integrates a delayed detached-eddy simulation (DDES) model with a parallel dynamic overset grid approach, enabling high-fidelity simulations of coupled aircraft carrier interactions. Validation confirms the accuracy of the precursor inflow method in reproducing air-wake characteristics and aerodynamic loads compared to full-domain simulations. Parametric analyses of 15 distinct landing trajectories reveal significant aerodynamic variability, particularly within 250 m of the carrier, where interactions with island-generated vortices induce fluctuations in lift (up to 25%), drag (18%), and pitching moments (30%). Ground effects near the deck further amplify load variations, while lateral deviations in landing paths generate asymmetric forces and moments. The proposed methodology demonstrates computational efficiency for multi-scenario analysis, providing critical insights into aerodynamic uncertainties during carrier operations.

Evolution of a tidal channel network in the Yellow River Delta, China, and simulation of optimization scenarios - Chengjie Xie; Baoshan Cui; Tian Xie; Shuling Yu; Zhonghua Ning (Journal of Environmental Management, 2024)

Longitudinal Dynamics of Hydrological Connectivity in the Yellow River Delta, China - Chengjie Xie; Baoshan Cui; Zhonghua Ning; Shuling Yu; Tian Xie (Frontiers in Marine Science, 2022)
River deltas are formed by the interaction of connecting water and sediment, and they are among the most economically and ecologically valuable ecosystems on Earth. Because of their special locations, together with direct and indirect human interference, river deltas are expected to be more vulnerable and fragmented. The increasing fragmentation of deltas is largely due to longitudinal hydrological connectivity disruption caused by human activities. However, the dynamics of longitudinal connectivity are unknown, especially in the Yellow River Delta (YRD), which has been subjected to heavy reclamation in recent years. In this study, we divided the whole YRD into three subregions, the erosion zone, the oilfield zone and the deposition zone, and then we used indicators to explore the spatiotemporal variation in hydrological connectivity on the whole scale and on the zonal scale of the delta during 1984-2018 in the YRD. We found that the variation in longitudinal hydrological connectivity was closely related to the geometry of the tidal channel networks, and that the changes in longitudinal hydrological connectivity varied with research scales. A weak increasing trend of connectivity was found on the whole scale of the delta during the past three decades. A decreasing trend of connectivity was found in both the erosion zone and the oilfield zone. In the deposition zone, however, the connectivity degree was enhanced. Furthermore, we also identified the key impaired area and relatively stable area of hydrological connectivity in the YRD and implied that the key impaired area may be a priority restoration zone of the impaired hydrological connectivity zone. Our study provides useful scientific guidance for the subsequent restoration of damaged wetlands.

Excretion kinetics of three dominant organochlorine compounds in human milk within the first 6 months postpartum - Shuling Song; Xiaodong Ma; Meng Pan; Ling Tong; Qin Tian (Environmental Monitoring and Assessment, 2018)

Residue levels of hexachlorocyclohexane and dichlorodiphenyltrichloroethane in human milk collected from Beijing - Shuling Song; Xiaodong Ma; Ling Tong; Qin Tian; Yi Huang; Shaoquan Yin; Hongbin Sun (Environmental Monitoring and Assessment, 2013)